ANALISIS KERENTANAN PETANI TERHADAP BAHAYA BANJIR DI KABUPATEN KARAWANG - Tommi, Tommi; Barus, Baba; Dharmawan, Arya Hadi (Jurnal Geografi, 2015)
Flood is one of the climate change phenomenon that often occurs in Karawang. Flood impact very big lossto the district community, mostly working in agriculture. The aim of this research is to analyze the extent ofdamage Citarum Upstream, analyzing the level of danger of flood in Karawang, and analyze thevulnerability of farmers in areas with high flood hazard. The method used in this research is the analysis ofthe level of damage Citarum upstream, analyzes the level of flood hazards and vulnerability analysis. Resultsfrom this study indicate the condition of Citarum upstream in rather bad condition, causing flooding in areasdownstream. Area in Karawang regency which has a high level of flood danger, namely the District WestTelukjambe, East Telukjambe, and District Jayakerta. Farmers in the village Karangligar susceptibilitylevels higher than the farmers in the village of Ciptamarga which is also an area with a high level of hazardof flooding. Suggestions for the solution of this research is the need to repair Citarum not only technicallybut also institutionally, the need to improve infrastructure, particularly irrigation facilities were damaged,and the need for agricultural insurance to farmers who experienced crop failure caused by flooding.